Phytochemical differences of hemp (Cannabis sativa L.) leaves from different germplasms and their regulatory effects on lipopolysaccharide-induced inflammation in Matin-Darby canine kidney cell lines - Liu, Yi; Xiao, Ai-Ping; Cheng, Hao; Liu, Liang-Liang; Kong, Kin Weng; Liu, Hong-Yan; Wu, Ding-Tao; Li, Hua-Bin; Gan, Ren-You (Frontiers in Nutrition, 2022)
The increasing demand of hemp (Cannabis sativa L.) has attracted more interest in exploring its phytochemical profile and bioactivities, such as anti-inflammatory effect. In this study, the phytochemicals of different hemp leaves were investigated, with the content order: total saponins content (TSC) > total alkaloids content (TAC) > total phenolics content (TPC) > total flavonoids content (TFC) > cannabinoids. Hemp leaves from Shanxi accumulated higher flavonoids and cannabinoids (i.e., THC, CBD, and CBN), while phenolics were more abundant in those from Hunan. A lipopolysaccharide (LPS)-induced inflammatory Matin-Darby canine kidney (MDCK) cell model was established to evaluate the anti-inflammatory effects of hemp leaf extracts. Hemp leaf extracts, especially the D129 and c7, significantly increased cell viability of LPS-induced inflammatory MDCK cells, and D132 significantly decreased the secretion of pro-inflammatory cytokines (TNF-α and IL-6) and the lactate dehydrogenase (LDH) activity. Except for c12, other hemp leaf extracts obviously decreased the cell morphological damage of LPS-induced inflammatory MDCK cells. The correlation analysis revealed that cannabinol (CBN) and TPC showed the strongest correlation with anti-inflammatory activities, and hierarchical clustering analysis also showed that hemp germplasms from Shanxi might be good alternatives to the common cultivar Ym7 due to their better anti-inflammatory activities. These results indicated that hemp leaves were effective in LPS-induced inflammatory MDCK cells, and flavonoids and cannabinoids were potential geographical markers for distinguishing them, which can provide new insights into the anti-inflammatory effect of hemp leaves and facilitate the application of hemp leaves as functional ingredients against inflammatory-related disorders.